The Paradox of Education for Sustainability (EfS): An Interpretive Inquiry into Teachers’ Engagement with Sustainability Policy Imperatives in a Western Australian Primary School - Kuzich, Sonja (Curtin University, 2019)
This ethnographic, interpretive research investigated how teachers at a Western Australian primary school interpreted and engaged with policy initiatives in Education for Sustainability (EfS). Through the dual concepts of affordance and paradox, representations of sustainability in macro and micro sustainability policy discourses were interrogated. Fragmentation and disorientation; dislocation of affordances; and deep inertia were found to be major obstacles that impeded the implementation of EfS.